HUBUNGAN DURASI PENGGUNAAN KOMPUTER DENGAN KELUHAN SHOULDER PAIN PADA KARYAWAN PERUSAHAAN KONTRAKTOR DI TANGERANG - Jennifer Putri Georgiani (2022)
Background : One of the health problems caused by long-term use of computers is musculoskeletal problems. The interaction between computer use and musculoskeletal use over 12 months was 15-52% for the upper extremities. Several studies have shown increased muscle activity according to people who use computers for long periods of time, causing chronic pain that limits the range of motion of joints, especially in the shoulder. Shoulder pain is one of the most common musculoskeletal disorders in Indonesia and the world, with subacromial pain syndrome (SAPS) being the highest presentation. Objective : This study aims to determine the relationship between shoulder pain complaints and computer users in contractor company employees in Tangerang. Method : based on the results of data processing using SPSS 25.0, 6 out of 20 (30%) respondents complained of mild pain and 14 of 20 (70%) respondents experienced moderate pain. After the correlation test, the pearson correlation coefficient for the duration of computer users and shoulder pain was obtained p=.099 with a significant value of p=.679. Conclusion : the conclusion of this study is that there is no significant relationship between the duration of computer users and complains of shoulder pain.